Solubility of calcium at stone monuments by acid rain - Aslan, F.; Arslan, M.; Eflatun, A. (My University, 2001)
In this study, historical monument samples, which were provided from Harput (in Elazi? in Turkey), were characterized. The effect of acid rain on these samples were investigated. The effects of pH, contact time and temperature on the solubility of calcium at the monuments were also examined. The concentrations of calcium in the run-off solutions are the highest at low pH. The maximum concentration of calcium at pH=2 and 25°C for one hour was found to be 190 mg/L for Esadiye Mosque(E1). The increasing of contact time and temperature also increases the erosion of the monuments.
Keywords: Acid rain; Erosion; Monuments; Solubility of calcium